Perbedaan Karakteristik Balita Stunting Di perkotaan Dan Pedesaan - Nur Aziza; Umar, Fitriani; Sari, Rasidah Wahyuni; Majid, Makhrajani (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
The prevalence of stunting is still quite high. Unbalanced food intake and a history of recurrent infectious diseases are direct causes of stunting. The purpose of this study was to determine the differences in the characteristics of stunted toddlers in urban and rural areas. This type of research is analytic with a cross-sectional study approach, the sample is all stunted toddlers aged 24-59 months in urban and rural areas, the sample is taken using purposive sampling method as many as 72 toddlers. The results of the study showed that the characteristics of parents, age of MP-ASI (p = 0.020), history of infectious diseases (p = 0.038), and socioeconomic status there were significant differences in stunting toddlers in urban and rural areas, while there was no significant difference between history Exclusive breastfeeding (p = 0.813), energy intake (p = 0.057), and protein intake (p = 0.386) in stunting toddlers in urban and rural areas. Suggested the need for increased knowledge of mothers.